Atraumatic splenic rupture in a child with COVID 19 - Ilirjana Bakalli; Marsela Biqiku; Durim Cela; Adnand Demrozi; Ermira Kola; Ermela Celaj; Inva Gjeta; Durim Sala; Dea Klironomi (BMC, 2022)
Abstract Background The majority of children with COVID-19 have only minor symptoms or none at all. COVID-19, on the other hand, can cause serious illness in some children, necessitating hospitalization, intensive care, and invasive ventilation. Many studies have revealed that SARS-CoV-2 affects not only the respiratory system, but also other vital organs in the body. We report here a child with an atraumatic splenic rupture as the initial and only manifestation of COVID-19. Case presentation A 13-year-old boy with clinical signs of acute abdomen, left-sided abdominal pain, and hemodynamic instability was admitted to the PICU in critical condition. His parents denied any trauma had occurred. In addition to imaging tests, a nasopharyngeal swab was taken for COVID-19 testing, which was positive. The thoracic CT scan was normal, whereas the abdominal CT scan revealed hemoperitoneum, splenic rupture, and free fluid in the abdomen. Conclusions The spleen is one of the organs targeted by the SARS-CoV-2. Splenic rupture, a potentially fatal and uncommon complication of COVID-19, can be the first and only clinical manifestation of the disease in children. All pediatricians should be aware of the possibility of atraumatic splenic rupture in children with COVID-19.